Biomolecular regulation, composition and nanoarchitecture of bone mineral - Atharva A. Poundarik (Nature Portfolio, 2018)
Abstract Tough natural nanocomposites like bone, nacre and sea sponges contain within their hierarchy, a mineral (phosphate, silicate or carbonate) phase that interacts with an organic phase. In bone, the role of mineral ultrastructure (organization, morphology, composition) is crucial to the mechanical and biological properties of the tissue. Better understanding of mineral interaction with the organic matrix, in particular non-collagenous proteins, osteocalcin (OC) and osteopontin (OPN), can lead to better design of biomimetic materials. Using small angle x-ray scattering (SAXS) and wavelength dispersive spectroscopy (WDS) on single (OC−/− and OPN−/−) and double (OC-OPN−/−;−/−) genetic knockout mice bones, we demonstrate that both osteocalcin and osteopontin have specific roles in the biomolecular regulation of mineral in bone and together they are major determinants of the quality of bone mineral. Specifically, for the first time, we show that proteins osteocalcin and osteopontin regulate bone mineral crystal size and organization in a codependent manner, while they independently determine crystal shape. We found that OC is more dominant in the regulation of the physical properties of bone mineral, while OPN is more dominant in the regulation of the mineral composition.